Electrical characterization of the diodes-based nanostructure ZnO:B - Yakuphanoğlu, Fahrettin; Caglar, Y.; Caglar, M.; Ilican, S. (Cambridge Univ Press, 2012)
The diodes-based undoped and boron (B) doped ZnO films deposited onto p-Si by sol-gel method using spin coating technique were fabricated. The morphological properties of ZnO films were analyzed by field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM) measurements. The results indicated that the surface morphology of the films was affected by the boron incorporation. The diode parameters were determined from the analysis of the measured dark current-voltage curves. The ideality factor of the diodes is higher than unity and was found to be 2.53, 2.36 and 2.17 for the undoped, 0.1% B-doped and 0.3% B-doped ZnO diodes, respectively. The obtained diode parameters like barrier height and ideality factor suggest that B dopant improves rectifying properties of the ZnO diode. The interface states density (D-it) of the diode was determined by conductance-voltage method and D-it values for the undoped, 0.1% B-doped and 0.3% B-doped ZnO diodes were found to be 8.26 x 10(11) eV(-1) cm(-2), 9.75 x 10(11) eV(-1) cm(-2) and 6.61 x 10(11) eV(-1) cm(-2), respectively. The obtained results indicate that the rectifying properties of the diodes-based nanostructure B-doped ZnO can be controlled by boron dopant.
Keywords: Spray-Pyrolysis Method; Thin-Films; Photovoltaic Properties; Temperature-Dependence; Optical-Properties; Schottky Diodes; Si; Heterojunction; Semiconductor; Nanorods